Clonal redemption and clonal anergy as mechanisms to balance B cell tolerance and immunity. Issue 1 (26th September 2019) - Burnett, Deborah L.; Reed, Joanne H.; Christ, Daniel; Goodnow, Christopher C.
Abstract: The adaptive immune system is tasked with producing antibodies that recognize a wide scope of potential pathogens, including those never before encountered, and concurrently avoiding formation of antibodies binding host tissues. The diverse repertoire of antibodies produced by V(D)J recombination inevitably includes autoantibodies that bind to self‐antigens, estimated to be as much as 70% of nascent antibodies on immature B cells. Early theoretical models of tolerance hypothesized that such self‐reactive clones could not possibly be allowed to survive and mature. However from the first direct view of the fate of nascent B cells carrying a self‐binding antibody it was clear that many "forbidden clones" circulate to secondary lymphoid tissues, where they adopt an IgM low IgD+ cell surface phenotype and are prevented from secreting autoantibodies by a series of tolerance checkpoints referred to as "clonal anergy." Since anergic B cells can be reactivated to secrete pathogenic autoantibodies in certain settings, the advantage of controlling self‐reactive antibodies by clonal anergy has until recently remained enigmatic. Here we review this topic and recent advances showing that anergic B cells are recruited into the germinal center to mutate away from self‐reactivity, undergoing "clonal redemption" into cells making antibodies with exquisite specificity for foreign immunogens.